Developing “Pick and Produce” Game to Teach Procedure Text for Third Year Senior High School Students (RETAIN, 2019)
AbstractWriting is one of English language productive skills which is considered difficult because before producing a good text, learners should be able to deliver the idea and then use proper language feature. According to 2013 Curriculum, standard competence of twelfth grade students is learning various genres of text; one of them is procedure text. Hence, a suitable instructional media is developed to teach procedure text for twelfth graders with less familiar topic. Recipe is known as common topic used in teaching procedure text, thus, the purpose of this study are describing the development of an instructional media involving game called “Pick and Produce” with less familiar topic such as manual (how to make something) and knowing students and teacher’s responses toward the game. It uses the modified cycle of R & D approach adopted from Dick, Carey and Carey (2015) to describe the development of the medium. The result shows that students and teacher give positive feedback toward the developed game. Furthermore, this medium helps students to gain their confidence during teaching learning activity and increase their better understanding of the topic (manual).Key words: Writing, Procedure text, Instructional media, EFL students, Pick and produce AbstrakMenulis adalah salah satu kemampuan produktif bahasa Inggris yang dianggap sulit karena sebelum menulis teks yang baik, pelajar harus mampu menyampaikan ide dan kemudian menggunakan struktur kebahasaan yang baik dan benar. Menurut Kurikulum 2013, standar kompetensi untuk siswa kelas 12 adalah mempelajari berbagai genre teks, salah satunya adalah teks prosedur. Oleh karena itu, sebuah media yang cocok untuk mengajar teks prosedur dikembangkan untuk mengajar siswa kelas 12 dengan topik yang kurang umum. Resep diketahui sebagai topik yang sangat umum digunakan untuk mengajar teks prosedur, oleh sebab itu, studi ini bertujuan untuk mendeskripsikan pengembangan sebuah media instruksional yang melibatkan permainan yang bernama “Pick and Produce” dengan topik yang kurang umum seperti manual (untuk membuat suatu benda) dan mengetahui respon yang diberikan siswa dan guru terhadap media yang dikembangkan. Studi ini menggunakan pendekatan R & D yang sudah dimodifikasi dari Dick, Carey dan Carey (2015) untuk mendeskripsikan pengembangan media. Hasil studi menunjukkan bahwa para siswa dan guru memberikan umpan balik yang positif terhadap media yang dikembangkan. Selain itu, media ini membantu para siswa untuk mendapatkan kepercayaan diri mereka selama aktivitas belajar-mengajar dan meningkatkan pemahaman mereka terhadap topik yang dibahas (manual).Kata kunci: Menulis, Teks prosedur, Media instruksional, Siswa EFL, Pick ad Produce